Factors affecting satisfaction and intention to repurchase retail banking services in Vietnam - Dao Cam Thuy; Nguyen Ngoc Quang (Cogent Business & Management, 2022)
Retail banking services of Vietnamese commercial banks are developing along with economic growth, improving the repurchase behavior of customers helps banks maintain a competitive edge in the market. Therefore, the research was conducted on factors affecting satisfaction and intention to repurchase retail banking (RB) services. This study builds and validates the Structured Equation Model (SEM) to assess the causal effect of factors such as service quality, brand reputation and customer trust on customer satisfaction and repurchase intention RB services of commercial banks in Vietnam. Survey results of 605 customers have shown that 6 factors affect positively the intention of individual customers to repurchase banking services. In the transition from satisfaction to intention to repurchase the services, there are two moderating variables included in the study, which are switching costs and commitment from the relationship. The research results can be suggestions to help customers improve their intention to use the services again at Vietnamese commercial banks.
Keywords: 650; brand reputation; customer satisfaction; repurchase intention; retail banking; service quality